Un Observatoire photographique participatif des paysages et de la valeur universelle de la Chaîne des Puys-faille de Limagne ? - Pierre Enjelvin; Claire Planchat; Fanny Cassani; Pierre-Alain Heydel; Danielle Fournioux (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Following requests from the Departmental Council of Puy de Dome, a photographic tool was created for the observation, evaluation and management of the Chaîne des Puys – faille de Limagne’s landscapes, in order for it to be inscribed as a UNESCO World Heritage Site. This article uses repeat photography to demonstrate the implementation process of the landscape dynamics observatory. Based on a participatory methodology for a photographic observatory of landscapes, this approach combines technical et participative devices in order to bring awareness to the different stakeholders: elected representatives and inhabitants of the registered territory, as well as landscapes and their multiple dimensions. We assume that the involvement of the photographic process, especially repeat photography, may promote Auteur0000-00-00T00:00:00Atheir ownership of the observatory, thereby ensuring its sustainability through management actions and other development procedures.